KEBIJAKAN HUKUM PIDANA TERHADAP TINDAK PIDANA DI BIDANG KETENAGAKERJAAN (Studi Kasus Pada Pengadilan Negeri Lubuk Pakam) - Prima, Aristo (Universitas Medan Area, 2016)
Status of employment law in the national legal order Indonesia theoretically can be separated into three areas, namely the areas of administration, the field of civil and criminal fields. Relationships law made by workers / laborers with employers included in the field of civil law. However, during the manufacturing process, implementation, and an end to the relationship controlled by the government. If during these processes there is a violation (not in accordance with applicable regulations), it can be applied to criminal sanctions. Based on this it raised the question of how the criminal law policy of the offenses in the field of employment, how goal setting normative regarding labor relations. The results of research and discussion to explain policies Criminal Law Against Crime in the Field of Employment is the regulation of provisions regarding the issue penal law in relation to employment issues in the legislation which is national that aims to maintain synchronization of the working relationship between employers and workers and put the government functions as a function harmonization between employers and workers. Goal setting normative concerning the employment relationship is to maintain order tangle working relationship between workers and employers.